Fight or flight - Michaels, Fern (Kensington Publishing Corp., 2025)
"From the comfort of her beautiful mountain-top retreat, Katherine Winston creates her bestselling young adult series, Girls with Unusual Powers. No one in the nearby small town has any idea of her true identity. To them, she's just the reclusive woman on the mountain, and Katherine is grateful to be left alone. It wasn't always this way. Though her parents were as neglectful as they were wealthy, Katherine built up a busy, full life. Then tragedy struck and she retreated, panic-stricken at the idea of engaging with anyone again. Aside from her two faithful dogs who provide companionship and security, Katherine mostly interacts with people anonymously online through reader fan pages. Now one of those fans appears to be in danger, and Katherine desperately wants to help. But that means moving beyond her isolated world for the first time in years. More and more, Katherine can't shake the feeling that some of her fears may be justified. Someone is watching her, she's sure of it, and they're getting closer all the time. And only by leaving her self-imposed exile can she hope to find the answers she needs, the courage to trust again, and an unexpected new beginning..."--